Impact of Child Caregiving Tasks on Pain & Fatigue: Results of a National Survey of Parents With Disabilities...American Occupational Therapy Association (AOTA) INSPIRE Annual Conference and Expo, April 3-5, 2025, Philadelphia, Pennsylvania. - Frauwirth, Stacy; Hayward, Katharine; Kirshbaum, Megan (American Journal of Occupational Therapy)
Date Presented 04/04/2025 New parents are at risk of repetitive strain and back injuries, and parents with disabilities face particular risk of secondary injuries. This session reports on a National Institute on Disability, Independent Living, and Rehabilitation Research–funded survey of parents with disabilities and discusses implications for OT. Primary Author and Speaker: Stacy Frauwirth Contributing Authors: Katharine Hayward, Megan Kirshbaum